Effect of monensin and essential oils on performance and energy metabolism of transition dairy cows. Issue 3 (28th November 2015) - Drong, C.; Meyer, U.; von Soosten, D.; Frahm, J.; Rehage, J.; Breves, G.; Dänicke, S.
Summary: This work examined preventive effects of a dietary and a medical intervention measure on postpartum (p.p.) ketogenesis in dairy cows overconditioned in late pregnancy. Sixty German Holstein cows were allocated 6 weeks antepartum (a.p.) to three high body condition score (BCS) groups (BCS 3.95 ± 0.08) and one low BCS group (LC, BCS 2.77 ± 0.14). Concentrate proportion in diet a.p. was higher (60% vs. 20%) and increase in proportion p.p. from 30% up to 50% decelerated (3 vs. 2 weeks) in high BCS groups. High BCS cows received a monensin controlled‐release capsule (CRC) (HC/MO), a blend of essential oils (HC/EO) or formed a control group (HC). Performance parameters and energy status were evaluated in three periods [day (d) −42 until calving, one until 14 days in milk (DIM), 15 until 56 DIM]. Feed efficiency was 65% and 53% higher in HC/MO than in LC (p < 0.001) and HC groups (p = 0.002) in the second period. Milk fat content was higher in HC/EO (5.60 vs. 4.82%; p = 0.012) and milk urea higher in HC/MO (135 mg/kg) than in LC cows (107 mg/kg; p < 0.001). Increased p.p. levels of non‐esterified fatty acids in serum were found in HC (p = 0.003), HC/MO (p = 0.068) and HC/EO (p = 0.002) in comparison with LC cows. Prevalence of subclinical and clinical ketosis was 54% and 46%, respectively, in HC group. Monensin decreased the prevalence to 50% and 7% respectively. Ruminal fermentation pattern showed higher proportions of propionate (23.43 mol % and 17.75 mol %, respectively; p < 0.008) and lower acetate:propionate ratio (2.66 vs. 3.76; p < 0.001) in HC/MO than HC group. Results suggest that a monensin CRC improved energy status and feed efficiency of transition dairy cows while essential oils failed to elicit any effect.